Robust, scalable and xeno-free protocol for differentiating human induced pluripotent stem cells into functional macrophages - De Homdedeu, Miquel; Escribá, Rubén; Rodríguez-González, Kenia; Querol, Sergi; Fernandez-Sojo, Jesus; Alvarez-Palomo, Belén (Frontiers in Immunology, 2026)
Human induced pluripotent stem cells (hiPSCs)-derived macrophages (iMacs) exhibit key macrophage phenotypic and functional properties, positioning them as promising candidates for allogenic cell immunotherapies. However, an efficient, scalable and good manufacturing practices (GMP)-compatible differentiation protocol is noticeably lacking. To meet this need, we aimed to develop a robust protocol for differentiating clinical-grade hiPSC lines into functional iMacs, designed for scalability and immediate GMP translation. We tested different media compositions, cytokine concentrations, seeding densities, culture regimens (2D vs. 3D) and coatings across key developmental stages. With the optimized protocol, we differentiated three different clinical-grade hiPSC lines towards mesoderm through embryoid body (EB) formation by agitation in 3D. Hematopoietic progenitor-producing EBs were induced to produce myeloid progenitors in agitation for 7 days. Then, myeloid progenitors were harvested and transferred to a G-Rex production platform to differentiate and further polarize into M1 or M2 iMacs. Cellular differentiation was assessed using flow cytometry panels through all developmental stages. At the final differentiated stage, iMacs were functionally characterized using the pHrodo phagocytosis assay. Pro-inflammatory cytokine secretion was analyzed by ELISA, and cell morphology was assessed by May-Grünwald Giemsa staining in Cytospin preparations. The full protocol was performed using feeder-free, scalable and either GMP or GMP- translatable reagents. This protocol enabled the production of iMacs with a mean purity of 98% viable cells, and a mean differentiation fold of 250X from a single hiPSC.